PATRIOTIC IDEAS IN THE CREATION OF ZAHIRIDDIN MUHAMMAD BABUR - Sultonova Umida Ortukovna (Journals Park Publishing, 2023)
This article talks about the ideas of patriotism in the works of Zahiriddin Muhammad Babur. The article discusses the life principles and philanthropic deeds of the great poet and statesman Zahiriddin Muhammad Babur. The experiences of the writer's personal life are expressed in a very bright and impressive way. Babur's poetry is dominated by the love of the country and the Motherland, the praise of noble human qualities and the depiction of noble feelings. Babur's humanitarian ideas are revealed through his creative works in India, the prosperity of the country and his services in bringing oriental culture.
Keywords: Zahiriddin Muhammad Babur, patriotic ideas, literature, poetry, ghazal, creativity, homeland, culture, enlightenment.